Multi-states Combination Nonlinear Control of In-wheel-motor-drive Vehicle Dynamics Stability. (May 2017) - Liu, Mingchun; Huang, Juhua; Chao, Ming
Abstract: A multi-states combination controller is presented to improve the dynamics stability of in-wheel-motor-drive (IWMD) vehicle. Based on the vehicle model with 14 degrees-of-freedom (DOFs), the proposed controller is designed and solved by using the nonlinear sliding mode algorithm, which generates the desired control variables to control vehicle velocity, yaw rate and side slip angle, cooperatively. The desired control variables, including the net longitudinal force, the net lateral force and the net yaw moment, are treated as the functions of the tyre longitudinal forces in the tyre coordinate system. Numerical simulation study is conducted to investigate the performance of the proposed controller. The simulation results show that the proposed multi-states controller significantly enhances vehicle dynamics stability over the single-state controller.